Penerapan Stock Control Pada Aplikasi Inventory-Ku Menggunakan Framework Laravel Dan Restful Webservices - Fifit Alfiah; Yohanes Agustinus Winardi; Mega Syahrani Utami; Lutfia Fauzia Dewi Aryanti; Martono Martono (ICIT Journal, 2024)
PT Global Trade Logistics Network (GTLN) is a shipping company that focuses on meeting the logistical needs of every customer by providing customs clearance services for imported goods. Through an online platform, the business aims to localize global trade and provide facilities for local and foreign products to flourish and thrive. Since the global trade logistics network's stockpiling system currently uses a semi-computerized system that uses Microsoft Excel, the study proposes the creation of an inventory control system for goods. Written data makes input and search for items difficult, inefficient, and ineffective. This creates an application program based on the Laravel Framework that uses the PHP programming language and Restful Web Services is used to share data between applications or systems. The program was created with the help of Visual Studio Code, a text editor that helps write the programming language to be created. A tool known as Xampp serves to provide software packages. This research will develop an inventory system that can track stocks in warehouses quickly and efficiently.